1982
DOI: 10.1159/000112663
|View full text |Cite
|
Sign up to set email alerts
|

Purified Mouse Schwann Cells: Mitogenic Effects of Fetal Calf Serum and Fibroblast Growth Factor

Abstract: We present an in vitro bioassay protocol for the detailed examination of mitogenic influences on purified mouse Schwann cells. This involves measurements of (i) increases in Schwann cell number per culture, (ii) incorporation of radiolabeled thymidine per culture, and (iii) the proportion of total Schwann cells that exhibit a labeled nucleus by autoradiography. Using this standard protocol we show that the mitogenic effects of fetal calf serum must be distinguished from its effects on cell retention to the cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…The relatively high rate of enteric glial cell divi sion in the absence of neurons is similar to the behaviour of purified populations of type 1 astrocytes [Raff et al, 1983], Schwann cells on the other hand divide relatively slowly and are stimulated to divide by axonal contact [Wood and Bunge, 1975], In a recent series of experiments aimed at expanding the num bers of glia in purified enteric glial cell cul tures, various growth factors were tested for their ability to promote glial cell prolifera tion. In table IV the results [Eccleston et al, 1987] are summarised and compared with similar results obtained with Schwann cells [Brockes et al, 1980;Krikorian et al, 1982;Pruss et al, 1982;Eccleston et al, 1987] and astrocytes [Brockes et al, 1980;Morri son and de Vellis, 1981;Pruss et al, 1982] in vitro. Thus, enteric glia behave similarly to astrocytes and Schwann cells in their re sponse to glial growth factor and fibroblast growth factor, but are similar to Schwann cells and dissimilar to astrocytes in their lack of response to epidermal growth factor.…”
Section: What Controls Cell Division In Enteric Glia?mentioning
confidence: 69%
“…The relatively high rate of enteric glial cell divi sion in the absence of neurons is similar to the behaviour of purified populations of type 1 astrocytes [Raff et al, 1983], Schwann cells on the other hand divide relatively slowly and are stimulated to divide by axonal contact [Wood and Bunge, 1975], In a recent series of experiments aimed at expanding the num bers of glia in purified enteric glial cell cul tures, various growth factors were tested for their ability to promote glial cell prolifera tion. In table IV the results [Eccleston et al, 1987] are summarised and compared with similar results obtained with Schwann cells [Brockes et al, 1980;Krikorian et al, 1982;Pruss et al, 1982;Eccleston et al, 1987] and astrocytes [Brockes et al, 1980;Morri son and de Vellis, 1981;Pruss et al, 1982] in vitro. Thus, enteric glia behave similarly to astrocytes and Schwann cells in their re sponse to glial growth factor and fibroblast growth factor, but are similar to Schwann cells and dissimilar to astrocytes in their lack of response to epidermal growth factor.…”
Section: What Controls Cell Division In Enteric Glia?mentioning
confidence: 69%
“…An impermeable polymer coat was deposited on the guide prior to implantation, which guided the proteins to release inwardly to the lumen. The mechanism for regeneration-promoting effect of b-FGF might be that it directly reacted with neural element or it indirectly enhanced the proliferation of Schwann cells [268,269]. It was also suggested that the supporting role of α1-GP in regeneration might be due to its involvement in preventing b-FGF from losing its activeness [268].…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Subcultures were treated 2-3 times with anti-Thy 1-2 (New England Nuclear, Mass., USA) and rabbit complement (Gibco) to eliminate the fibroblasts. The remaining Schwann cells (95-98%) were plated in DMEMHam F'10 with 10% FCS and maintained in 2% FCS [29] at a concentration of 2 x KF cells per 35-mm2 dish. Monoclonal anti body 6.17, a Schwann cell marker [32], was used to evaluate the purity of the Schwann cells.…”
Section: Schwann Cell Culturesmentioning
confidence: 99%
“…lc) are consistent with the idea that Schwann cell proliferation is regulated by the balance of mitogenic and inhibitory autocrine factors [42] and/or by a decline in the level of receptors [46] on Trembler cells. Thus, the active division of 1-day-old mouse Schwann cells may result from the secretion of autocrine growth factors [44,45], associated or not with axolemma [47], or from the presence of a mitogenic factor in the FCS [29]. At this stage, these factors would be equally active on mutant and normal Schwann cells because the 'inhibitory activ ity' would be very low and/or the level of receptors iden tical.…”
Section: Age-related Proliferation O F Schwann Cellsmentioning
confidence: 99%
See 1 more Smart Citation